Green Energy—Green for Whom? A Case Study of the Kabinakagami River Waterpower Project in Northern Canada - Stephen R. J. Tsuji; Dan D. P. McCarthy; Stephen Quilley (Sustainability, 2021)
Green energy has become a term that heralds efforts of environmental conservation and protection worldwide; however, much of it is marred with questions of what it means to be green. More precisely, it has become a question of Green for whom? While many of the impacts of supposed green energy projects are local in their reach, some may be more regional in their scope, such as hydroelectric power. Hydroelectric power generation negatively impacts the environment and people who rely on the environment for sustenance, such as, Indigenous peoples of northern Canada. Taking into account their position with respect to the areas impacted by these green projects, many Indigenous peoples have voiced their concerns and doubts concerning green energy, which is purported to be a mode of energy production that champions the environment. The Kabinakagami River Waterpower Project serves as a case study for both the potential effects of the project and the different views associated with these endeavors. If nothing else, the accounts and testimonies found within shall stand as a testament to the hubris of calling an energy project green without properly assessing and considering the impacts. While these statements relate to the case presented, they also carry significance in the wider world due to the numerous Indigenous communities around the world that are having their spaces slowly being encroached upon in the name of sustainable growth, or green energy. This will especially be true in the post-COVID-19 period where green energy and a green economy are being touted as a way towards state and worldwide recovery.